2007
DOI: 10.1089/aid.2006.0240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods to Detect Recent HIV Type 1 Infection in Cross-Sectionally Collected Specimens from a Cohort of Female Sex Workers in the Dominican Republic

Abstract: Interest in estimating HIV-1 incidence using specimens obtained as part of cross-sectional surveys has led to the development of new methods to detect recent HIV-1 infection through the testing of a single anti-HIV-positive specimen. These assays are based on quantitative and qualitative differences in anti-HIV-1 antibodies between recent and long-standing infections. An ongoing vaccine preparedness study enrolled female sex workers in the Dominican Republic. Specimens from women found to be HIV positive at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…1 But such protocols and the use of clinical information to improve assay performance are unlikely to be feasible in resource-constrained setting. The essential problem in using the BED method to estimate HIV incidence thus continues to lie in the lack of unequivocal identification of persons with long-term HIV infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 But such protocols and the use of clinical information to improve assay performance are unlikely to be feasible in resource-constrained setting. The essential problem in using the BED method to estimate HIV incidence thus continues to lie in the lack of unequivocal identification of persons with long-term HIV infections.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Although some success has been achieved, obstacles still remain to widespread use of these methods, especially in the developing world, where such methods and technologies are most urgently required. 1,9 The most reliable way of measuring HIV incidence is following up HIV-uninfected but susceptible cohorts, measuring new infections over specified time periods. This, however, is subject to a number of biases, is expensive, and involves following up large numbers of people over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…However, low CD4 counts and viral load, as well as antiretroviral treatment, had no effect in the AI 32 . Comparative studies of the avidity assay with detuned or BED-CEIA showed similar performances for the three assays to identify recent infections in a region where subtype B predominates 35 . More recently, evaluating known seroconversion rates of HIV-seropositive samples from Uganda, where subtypes D and A predominate, the mean AI found for patients with recent infection was 0.55±0.21, while AI of 0.93±0.14 was detected for those from long-term infections 36 .…”
Section: Avidity Index Methods •mentioning
confidence: 89%
“…Since currently there is no agreement which RITA assay is accurate and robust enough for the intended use, and no single test fulfills the required characteristics, the use of a combination of 2 or more assays has been suggested [34,51]. It was also proposed to apply algorithms including clinical status and information such as T CD4 + cell count, and/or HIV RNA testing, and/or determination of antiretroviral use for the purpose of achieving the most accurate detection of recent HIV infection [3,5,38].…”
Section: Methods Based On the Viral Markersmentioning
confidence: 99%